Heteronuclear d–d and d–f Ru(ii)/M complexes [M = Gd(iii), Yb(iii), Nd(iii), Zn(ii) or Mn(ii)] of ligands combining phenanthroline and aminocarboxylate binding sites: combined relaxivity, cell imaging and photophysical studies. Issue 18 (16th April 2019) - Crowston, Bethany J.; Shipp, James D.; Chekulaev, Dimitri; McKenzie, Luke K.; Jones, Callum; Weinstein, Julia A.; Meijer, Anthony J. H.; Bryant, Helen E.; Natrajan, Louise; Woodward, Adam; Ward, Michael D.
Abstract : d/d and d/f heterodinuclear and heterotrinuclear complexes were studied for their photophysical and imaging properties. Abstract : A ligand skeleton combining a 1, 10-phenanthroline (phen) binding site and one or two heptadentate N3 O4 aminocarboxylate binding sites, connected via alkyne spacers to the phen C 3 or C 3 /C 8 positions, has been used to prepare a range of heteronuclearRu·M andRu·M2 complexes which have been evaluated for their cell imaging, relaxivity, and photophysical properties. In all cases the phen unit is bound to a {Ru(bipy)2 } 2+ unit to give a phosphorescent {Ru(bipy)2 (phen)} 2+ luminophore, and the pendant aminocarboxylate sites are occupied by a secondary metal ionM which is either a lanthanide [Gd(iii ), Nd(iii ), Yb(iii )] or another d-block ion [Zn(ii ), Mn(ii )]. WhenM = Gd(iii ) or Mn(ii ) these ions provide the complexes with a high relaxivity for water; in the case ofRu·Gd andRu·Gd2 the combination of high water relaxivity and 3 MLCT phosphorescence from the Ru(ii ) unit provides the possibility of two different types of imaging modality in a single molecular probe. In the case ofRu·Mn andRu·Mn2 the Ru(ii )-based phosphorescence is substantially reduced compared to the control complexesRu·Zn andRu·Zn2 due to the quenching effect of the Mn(ii ) centres. Ultrafast transient absorption spectroscopy studies onRu·Mn (andRu·Zn as a non-quenched control) reveal the occurrence of fast (<1 ns) PET inRu·Mn, from the Mn(ii ) ion to the Ru(ii )-based 3 MLCT state, i.e. Mn II –(phen˙ − )–Ru III → Mn III –(phen˙ − )–Ru II ; the resulting Mn III –(phen˙ − ) state decays with τ ≈ 5 ns and is non-luminescent. This occurs in conformers when an ET pathway is facilitated by a planar, conjugated bridging ligand conformation connecting the two units across the alkyne bridge but does not occur in conformers where the two units are electronically decoupled by a twisted conformation of the bridging ligand. Computational studies (DFT) onRu·Mn confirmed both the occurrence of the PET quenching pathway and its dependence on molecular conformation. In the complexesRu·Ln andRu·Ln2 (Ln = Nd, Yb), sensitised near-infrared luminescence from Nd(iii ) or Yb(iii ) is observed following photoinduced energy-transfer from the Ru(ii ) core, with Ru → Nd energy-transfer being faster than Ru → Yb energy-transfer due to the higher density of energy-accepting states on Nd(iii ).